2013
DOI: 10.1002/chem.201203607
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Nanoplatelets: Electrochemical Properties and Applications for Oxidation of Endocrine‐Disrupting Chemicals

Abstract: In most graphene-based electrochemical applications, graphene nanoplatelets (GNPs) have been applied. Now, for the first time, electrochemical properties of GNPs, namely, its electrochemical activity, potential window, and double-layer capacitance, have been investigated. These properties are compared with those of carbon nanotubes (CNTs). GNP- and CNT-coated electrodes were then applied for electrochemical oxidation of endocrine-disrupting chemicals. The GNP-coated electrode was characterized by atomic force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 122 publications
1
24
0
Order By: Relevance
“…It has been reported that GNPs are suitable for electrochemical detection and removal of endocrine-disrupting chemicals, 32 nanocomposite cancer sensors, 33 nanoparticle decorated cholesterol sensors, 34 and detectors of biomarkers to name a few. 35 It is therefore essential to understand the mass transport properties of graphene materials to assist their application in biotechnology and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that GNPs are suitable for electrochemical detection and removal of endocrine-disrupting chemicals, 32 nanocomposite cancer sensors, 33 nanoparticle decorated cholesterol sensors, 34 and detectors of biomarkers to name a few. 35 It is therefore essential to understand the mass transport properties of graphene materials to assist their application in biotechnology and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene can be directly used to modify the electrode. For example, Wan et al [83] investigated the electrochemical properties of graphene nanoplatelets on a GCE and used the GCE for detection of endocrine-disrupting chemicals (i.e., BPA, 2,4-dichlorophenol, and octylphenol).…”
Section: Electrochemical Sensors Based On Carbon Nanomaterialsmentioning
confidence: 99%
“…Another study showed that PANi coated magnetic nanocomposite was capable of removal of chromium, as well as reduction of hexavalent to trivalent state . Recently, graphene and graphene oxide (GO) have attracted tremendous interest due to their special 2D nanostructures and fascinating properties . The decoration or functionalization onto graphene nanosheets facilitate the decrease of the aggregation of graphene nanosheets and guarantee the large specific surface area.…”
Section: Introductionmentioning
confidence: 99%